APPLICATION OF HPLC-BASED METABOLOMICS TO IDENTIFY RETENTION TIMES ANTIBACTERIAL COMPONENTS OF Stapylococcus aureus FROM KECOMBRANG FLOWER EXTRACT (Etlingera elatior) - Wahyu Haryati Maser; Nancy Dewi Yuliana (UNIVERSITAS SEBELAS MARET (UNS), 2017)
Kecombrang (Etlingera elatior) is a well-known herb in Indonesia that is widely used in traditional medicine and as a flavour in local dishes. The aim of this study was to identify retention time of antibacterial components from kecombrang flower extract (Etlingera elatior) by HPLC-based metabolomics method. The antibacterial activity of ethanol extracts, chloroform, and water fractions was assessed by well-diffusion agar method against Staphylococcus aureus. Only chloroform fraction showed medium inhibition activity against Staphylococcus aureus. The HPLC chemical profiles of the fractions were then correlated to their antibacterial activity profile by means of Orthogonal Projection to Latent Sructure (OPLS) analysis. Peak area with retention time of 0.96 - 1.12 min present in chloroform fraction at UV 250 nm was found to significantly correlate to the antibacterial activity (Y related coefficient value 0.73).